Tracing the origin of the malay race through the morphological, historical, socio-cultural and genetic analyses - Zainuddin, Zafarina (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
The uniparenlally inherited mitochondrial DNA (mtDNA) is in the limelight for the past two decades, in studies relating to demographic bistoJy of mankind and in foreosic kinship testing. Jn this study, human mtDNA hypervariable segments I, 2, and 3 (HVI, HV1, and HV3) were anal)'7.ed in 248 uorelated Malay individuals in Peninsular Malaysia. Combined analyses of HVI, HV2, and HV3 · revealed a total of 180 mtDNA haplotypes with 149 unique haplotypes and 31 haplotypes occmring in more than one individual. The geoetic diversity was estimated to be 99.47%, and the probability of any two individuals sharing the same mtDNA haplotype was 0.93%. The most frequeot mtDNA haplotype (73, 146, 150, 195, 263, 315.IC, 16140, 16182C, 16183C, 16189, 16217, 16274, and 16335) was shared by 11 (4.44%) individuals. The nucleotide diversity and mean of pair-wise differences were found to be 0.0